2002
DOI: 10.2135/cropsci2002.0105
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Transgenic and Classical Sources of Resistance

Abstract: of the disease include light green and yellow streaking of the leaves as well as curling of the leaves due to mite The development of wheat (Triticum aestivum L.) cultivars that activity. Infected plants typically exhibit stunted growth, are resistant to Wheat streak mosaic virus (WSMV), yet competitive in yield under nondiseased conditions, is an objective for breeding Published in Crop Sci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…In our previous studies, we had examined nine different ULGCS lines for five generations under greenhouse conditions and found the trait to be heritable and stable (Rathore et al ., ; Sunilkumar et al ., ). As mentioned earlier, there are reports showing that transgene efficacy that was observed under greenhouse conditions either weakened or showed variability under field conditions (Bahieldin et al ., ; Brandle et al ., ; Dietz‐Pfeilstetter, ; Sharp et al ., ; Stam et al ., ). Prior to our use of RNAi to obtain the ULGCS trait, we had attempted to employ antisense technology to achieve the same objective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we had examined nine different ULGCS lines for five generations under greenhouse conditions and found the trait to be heritable and stable (Rathore et al ., ; Sunilkumar et al ., ). As mentioned earlier, there are reports showing that transgene efficacy that was observed under greenhouse conditions either weakened or showed variability under field conditions (Bahieldin et al ., ; Brandle et al ., ; Dietz‐Pfeilstetter, ; Sharp et al ., ; Stam et al ., ). Prior to our use of RNAi to obtain the ULGCS trait, we had attempted to employ antisense technology to achieve the same objective.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sharp et al . () observed that transgenic wheat plants expressing viral coat proteins against wheat mosaic virus were resistant in greenhouse studies, but lost this trait in the field. In a separate study conducted on wheat, researchers reported that the effect of transgene expression varied from year to year, based on the climatic conditions of a particular growing season (Bahieldin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…While field evaluations need to be undertaken, as often transgenes in wheat are not effective under field conditions (Sharp et al, 2002), this study provides evidence that the transgene is not temperature sensitive. This work has confirmed that the transgenic hairpin is effective at temperatures up to 24°C.…”
Section: Discussionmentioning
confidence: 79%
“…To date, Wsm1 is the only named gene conferring resistance to WSMV (Friebe et al, 1991) and being used in cultivar improvement (Baley et al, 2001; Sharp et al, 2002; Divis et al, 2006). Wsm1 was transferred from Th.…”
mentioning
confidence: 99%
“…Although Wsm1 confers a high level of resistance to WSMV under field conditions, the presence of the T4DL·4Ai#2S translocation had detrimental effects on bread‐making quality and other agronomic parameters (Seifers et al, 1995). Baley et al (2001) and Sharp et al (2002) analyzed the effect of the T4DL·4Ai#2S translocation under inoculated and noninoculated conditions in Montana spring wheats. Wsm1 provided a high level of resistance in the presence of the virus but, under noninoculated conditions, the presence of the T4DL·4Ai#2S translocation caused an 11 to 28% decrease in grain yield.…”
mentioning
confidence: 99%